Effect of Short-Term Aging Process on the Moisture Susceptibility of Asphalt Mixtures and Binders Containing Sasobit Warm Mix Additive - Bo Li; Jinyu Yang; Xiaohui Li; Xiang Liu; Feng Han; Liangying Li (Advances in Materials Science and Engineering)
Moisture susceptibility is one of the key issues of warm mix asphalt (WMA). In this research, the moisture susceptibility of asphalt mixtures and binders containing Sasobit warm mix additive was investigated in comparison to that of hot mixture asphalt (HMA) through laboratory aging experiments. The WMA asphalt mixtures were aged in the laboratory at three aging temperatures and times. The moisture susceptibility of the asphalt mixtures was measured through the laboratory immersed Marshall test and freeze-thaw splitting test. The surface free energy (SFE) of asphalt binders extracted from WMA asphalt mixtures was determined by the sessile drop method. The results show that the aging time and temperature have a significant effect on the improvement in moisture susceptibility in terms of both the freeze-thaw splitting strength ratios and the residual Marshall stability of asphalt mixtures containing Sasobit warm mix additive. The SFE of asphalt binders extracted from Sasobit warm mix increased with the aging time and temperature. The moisture susceptibility of the asphalt mixtures and binders containing Sasobit warm mixes was similar to or even greater than that of HMA aging under certain conditions.